Effect of Silver (Ag) Addition on the Forming Of Y-247 Superconductors (Y2Ba4Cu7O15-?) using Wet Mixing Method - Putra, A.A. Made Wisnu Wijaya; Suharta, W. G.; Suardana, P. (BULETIN FISIKA, 2019)
Superconductor Y-247 (Y 2 Ba 4 Cu 7 O 15-? ) with adding silver (Ag) by using the wet-mixing method has been done. The synthesis process was carried out by calcination at 600 o C for 3 hours and sintered at 925 o C for 10 hours. Variations in the increase in the addition of Ag used were Ag 0.05 , Ag 0.1 , Ag 0.15 and Ag 0.2 . Characterization of X-Ray Diffraction (XRD), showed an increase in the addition of Ag resulting in a decrease in the volume fraction, where the volume fractions obtained consecutive were 55.0%, 51.3%, 50.9% and 46.3%. Increasing the addition of Ag results in an increase in the lattice parameter values in the direction of the a axis which is 3.8247 Å, 3.8291 Å, 3.8292 Å, 3.8293 Å, decreasing the lattice parameter values in the b axis direction which is 3.8426 Å, 3.8415 Å, 3.8409 Å, 3.8383 Å and decreasing the lattice parameter values in the direction of the c axis are 49.2174 Å, 49.2022 Å, 49.1881 Å, 49.1761 Å. Analysis of the results of the characterization of Scanning Electron Microscopy (SEM), the particle size obtained was 225.47 nm, 202.88 nm, 190.68 nm and 172.22 nm.